THE IMPLEMENTATIONOF CRITICAL READING STRATEGIES ON EFL STUDENTS’ READING COMPREHENSION IN THE TKACONTEXT: EXAMINING GENDER AS AMODERATING VARIABLE - Winda Mala Sari; Ratmanida (University of Kuningan, 2026)
Reading comprehension remains a major challenge for Indonesian senior high school students, particularly in responding to higher-order thinking questions assessed in national examinations such as the Tes Kemampuan Akademik (TKA). This study investigates the effectiveness of critical reading strategies in improving twelfth-grade students’ reading comprehension and examines whether gender moderates the effect of the instructional strategy. Employing a quasi-experimental pre-test–post-test factorial design, the study involved twelfth-grade students of SMA IBS Raudhatul Jannah Payakumbuh, who were assigned to an experimental group taught using critical reading strategies and a control group taught using conventional methods. The instructional intervention integrated previewing, annotating, questioning, summarizing, and evaluating arguments. Reading comprehension data were collected through standardized reading tests aligned with TKA indicators and analyzed using two-way ANOVA. The findings reveal that students taught through critical reading strategies significantly outperformed those taught through conventional instruction. Female and male students in the experimental group both demonstrated higher post-test scores than their counterparts in the control group. However, the interaction between teaching strategy and gender was not statistically significant, indicating that critical reading strategies benefited students regardless of gender. These results suggest that explicit instruction in critical reading strategies is an effective pedagogical approach for enhancing reading comprehension and preparing students for the cognitive demands of the TKA. The study offers practical implications for English teachers and contributes empirical evidence to the growing body of EFL reading research in secondary education.